Внесок українських вчених у розвиток квантової фiзики - Korsun, I. V. (Publishing house "Academperiodika", 2018)
The contribution of Ukrainian scientists to the development of quantum physics has been analyzed, and a classification in accordance with corresponding branches has been made. The importance of researches in this physical domain is demonstrated. The priority of Ukrainian scientists in a number of scientific issues in the world science is shown. Attention is paid not only to the scientific activity of physicists, but also to their pedagogical and educational works. The importance of current researches carried out by Ukrainian scientists is demonstrated.